Pisco in the independence of Peru - Sifuentes Alemán, José Ítalo (2020)
Based on primary historical documents of Peru, the biography of Pisco between 1819 and 1826 is presented, a period that includes the years before and after the proclamation of national independence. In these documents are recorded the acts of management of the first rulers and public officials of the nascent republic, patriots of Argentine, Chilean, Colombian and Peruvian origin. It was these authorities who two centuries ago ratified that the origins of pisco are in Peru. The results of this research in historical documents also show the vitality of our this product, which dates back to the beginning of the 17th century.